2017
DOI: 10.1128/jvi.01055-17
|View full text |Cite
|
Sign up to set email alerts
|

Screening of FDA-Approved Drugs for Inhibitors of Japanese Encephalitis Virus Infection

Abstract: Japanese encephalitis virus (JEV), an arthropod-borne flavivirus, is a major cause of acute viral encephalitis in humans. No approved drug is available for the specific treatment of JEV infections, and the available vaccines are not effective against all clinical JEV isolates. In the study described here, a high-throughput screening of an FDA-approved drug library for inhibitors of JEV was performed. Five hit drugs that inhibited JEV infection with a selective index of >10 were identified. The antiviral activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 47 publications
(50 reference statements)
1
94
0
1
Order By: Relevance
“…All three tested blockers reduced PDCoV yields significantly. Previous studies revealed that these blockers also exhibited inhibitory effects on the replication of the IAV, WNV, DENV and Japanese encephalitis virus (JEV) through different mechanisms (Dionicio et al, 2018;Fujioka et al, 2018;Scherbik and Brinton, 2010;Wang et al, 2017). The L-type calcium channel is a wellstudied calcium channel and the main route for calcium entry into cells (Kabir et al, 2016;Robin and Allard, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…All three tested blockers reduced PDCoV yields significantly. Previous studies revealed that these blockers also exhibited inhibitory effects on the replication of the IAV, WNV, DENV and Japanese encephalitis virus (JEV) through different mechanisms (Dionicio et al, 2018;Fujioka et al, 2018;Scherbik and Brinton, 2010;Wang et al, 2017). The L-type calcium channel is a wellstudied calcium channel and the main route for calcium entry into cells (Kabir et al, 2016;Robin and Allard, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…JEV infection-related clinical symptoms include fever, headache, vomiting, diarrhea, mental status changes, and signs of meningeal irritation (5); the ratio of survival with psychiatric sequelae or permanent neurological is approximately 44% (6). Although the morbidity and mortality decreased with the use of various vaccines, and several recent researchers have identified a number of compounds with anti-JEV activities, such as N-nonyl-deoxynojirimycin (7), dehydroepiandrosterone (8), N-methylisatin-beta-thiosemicarbazone derivative (SCH 16) (9), indirubin (10), manidipine (11), chlorpromazine (12), etanercept (13), and minocycline (14), few therapies beyond intensive supportive care to treat patients with JEV are available.…”
Section: J Apanese Encephalitis Virus (Jev) Is a Member Of The Genus mentioning
confidence: 99%
“…This is the case for mycophenolic acid, niclosamide, nanchangmycin, cloroquine, and other antimalarial drugs. On the other hand, independent DR screenings against Japanese encephalitis virus (JEV), HCV, and dengue virus (DENV) led to the identification of antiviral activity of different FDA-approved drugs [25][26][27]. In particular, the dopamine D2 receptor antagonist prochlorperazine was identified as a potent inhibitor of HCV and DENV that acts by interfering with virus attachment and entry [26,28].…”
Section: Drug Repurposing For Rna Virus Infectionsmentioning
confidence: 99%